The game: a didactic strategy to strengthen the reading process - Arrieta Mier, Maira Esther; Mieles Palacín, Juana Judith; González Roys, Gustavo Adolfo (Revista Criterios, 2023)
The reading process is multiple since within it complex thinking skills underlie and, through this process, we can have a more critical and reflective look at the world around us. It is also clear that it is necessary to seek strategies that contribute to strengthening the reading process in students. In this article, the game is addressed in different reading situations, and how it can be established as a very important didactic strategy to strengthen the process. In addition, the article gives an account of how various authors have significantly investigated playfulness and its incidence in reading processes. The results showed an improvement in this process of the students, in terms of the literal comprehension of texts at different levels. It was concluded that the playful activities managed to capture their interest and improve concentration when reading or interpreting questions related to the texts.